The Effect Of Sawdust And Chaff Media Storage OnCocoa (Theobroma Cacao L.) Seeds Viability - Muchammad Toyyib; Bambang Gunawan; Bambang Wicaksono Hariyadi (Faculty of Agriculture, Merdeka University Surabaya, 2017)
The objective of the research is to determine the effect of sawdust and chaff media storage on viability of cocoa (Theobroma cacao L.) seeds. Cocoa seeds’ viability need to be maintained during storage/shipment to planting destination. The research uses simple group randomized design (RAK)consisting of five (5) treatment with three (3)replicates. Assignment of treatment is carried out in randomized trial plots. The varieties tested is F1 hybrid varieties obtained from Indonesia Coffee and Cocoa Research Center. The parameters observed included percentage (amount) of germination, rate of germination, and gross weight of sprouts. The result indicates shows that media storage treatment using sawdust and chaff provides significant effect on the percentage (number) of seeds germinate, sprout and speed or rate of gross weight of cocoa seed sprouts. In addition, control treatment (storage without chaff or sawdust) resulted in the highest percentage (number) of germinated seed, while the highest germination rate and gross weight of sprouts is indicated by treatment of storage with chaff of 100% although not significantly different statistically with 50% chaff.